Bicalutamide 25 mg combined with minoxidil 1 mg versus minoxidil 1 mg for female pattern hair loss: A randomized double-blind clinical trial - Libório, Ricardo da Silva [UNESP]; Motta, Adriana Viana da; Miot, Hélio Amante [UNESP]; Müller Ramos, Paulo [UNESP] (Elsevier, 2025)
Background: Antiandrogenic drugs are often used to treat female pattern hair loss (FPHL) despite limited evidence supporting their use. There is growing interest in bicalutamide for this purpose, but its efficacy in treating FPHL has not been evaluated in clinical trials. Objectives: To assess the efficacy of 25 mg/d bicalutamide combined with 1 mg/d minoxidil compared to 1 mg/d minoxidil monotherapy over 24 weeks for FPHL treatment. Methods: A randomized, controlled, double-blind clinical trial enrolled 74 participants into 2 groups: bicalutamide 25 mg/d plus minoxidil 1 mg/d or placebo plus minoxidil 1 mg/d for 24 weeks. The primary outcome was the change in total hair density in the target area. Result: Sixty-four (86.5%) participants completed the study (32 per group). There was a mean increase of 18.1 hairs/cm2 in the bicalutamide-minoxidil group and 21.5 hairs/cm2 in the minoxidil group (P = .86). According to the global consensus analysis of clinical photographs, there was no difference in clinical improvement between the groups (P = .78). Limitations: Single-center study and short follow-up period (24 weeks). Conclusion: Bicalutamide 25 mg/d combined with minoxidil 1 mg/d did not provide additional improvement in FPHL treatment compared to minoxidil alone after 24 weeks.
Keywords: androgenetic alopecia; bicalutamide; female pattern hair loss; oral minoxidil; treatment; woman